Financial Behavior in the Digital Era: Integrating Financial Knowledge, Attitudes, Planning, and FinTech - M. Trihudiyatmanto (Jurnal Akuntansi, Manajemen dan Perbankan Syariah, 2025)
Purpose - This study was conducted to examine the impact of financial knowledge, financial attitudes, financial planning, and financial technology on the financial behavior of unmarried Gen Z individuals aged 18–27 in Wonorejo Selomerto, Wonosobo. Method -Using a purposive sampling technique (non-probability sampling), data were collected from 144 respondents and analyzed via multiple linear regression. Findings - The findings demonstrate that all independent variables exert a positive and significant influence on financial behavior when analyzed individually: financial knowledge (t-calc=3.746 > t-table=1.65581; sig=0.000 < 0.05), financial attitudes t-calc=27.157 > t-table=1.65581; sig=0.000 < 0.05), financial planning t-calc=2.389 > t-table=1.65581; sig=0.018 < 0.05), and financial technology t-calc=4.256 > t-table=1.65581; sig=0.000 < 0.05). Implications - The implications of this study are valuable for Gen Z in Wonorejo Selomerto in understanding the importance of financial knowledge, financial attitudes, financial planning, and financial technology for better financial behavior management.